Two individuals with potential monkeypox virus reinfection - Raccagni, Angelo Roberto; Canetti, Diana; Mileto, Davide; Tamburini, Andrea Marco; Candela, Caterina; Albarello, Luca; Bracchitta, Fiorenza; Mancon, Alessandro; Micheli, Valeria; Gismondo, Maria Rita; Castagna, Antonella; Nozza, Silvia (The Lancet infectious diseases, 2023)
Over 80 000 mpox (formerly known as monkeypox) cases have been confirmed worldwide and recovered individuals are considered protected against reinfection.1–3 However, an individual with apparent reinfection has been recently reported.4 In this Comment we describe two individuals with potential monkeypox virus reinfection at San Raffaele Hospital, Milan, Italy (figure; see appendix for details on testing and results). Monkeypox virus PCR was positive for lesion, rectal, and oropharyngeal swabs with cycle threshold values ranging between 18 and 32, with concurrent chlamydia proctitis. Anoscopy revealed mucosal congestion with erosions and ulcerations, and a rectal swab was positive for both monkeypox virus with a cycle threshold value of 37, and for chlamydia.